Wildoak - Harrington, C. C. (Scholastic Press, 2022)
Bullied for her stutter in a 1960s English school, eleven-year-old Maggie Stephens takes drastic action that gets her expelled. Maggie is then sent to live with her doctor grandfather in rural Cornwall in the hopes that he can help her. Maggie quickly bonds with her loving grandfather and finds solace in the nearby woods of Wildoak Forest. There, she makes an astonishing discovery: a baby snow leopard has been abandoned and its life is threatened. In alternating chapters, readers learn how the snow leopard came to live in the forest, and how Maggie overcomes her fear of public speaking to become the animal's advocate.